Proceedings of the 15th International Symposium on Management (INSYMA 2018) 2018
DOI: 10.2991/insyma-18.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

Factors determinant of bank capital buffer: empirical study on islamic rural banking in Indonesia

Abstract: Capital is a very important aspect of the banking industry as it will be used to cover the losses suffered by the bank. Financial Services Authority set a minimum limit of the bank's capital adequacy ratio of 8%. This study aims to determine the size of capital buffer. There are several factors believed to determine the amount of capital buffer, such as the return on assets (ROA), non-performing financing (NPF), financing to deposit ratio (FDR), the net profit margin (NPM), and the ratio of operating expenses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 4 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…This is possible because it turns out that LDR is not able to increase profitability (Masood et al, 2013), even the results of this study have a negative effect on the capital buffer. This finding supports the findings by Sutrisno (2018) and Haryanto (2015), who found an insignificant effect of LDR with capital buffer. While different results were found by Eliskovski (2014) and Belém and Gartner (2016) who showed a significant effect between LDR and capital buffer.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is possible because it turns out that LDR is not able to increase profitability (Masood et al, 2013), even the results of this study have a negative effect on the capital buffer. This finding supports the findings by Sutrisno (2018) and Haryanto (2015), who found an insignificant effect of LDR with capital buffer. While different results were found by Eliskovski (2014) and Belém and Gartner (2016) who showed a significant effect between LDR and capital buffer.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with the findings by Belém and Gartner (2016) who found the effect of previous capital buffers. Likewise, Wong et al (2008) in America and Sutrisno (2018) in Indonesia also found the effect of previous CAR with a capital buffer. In contrast, Hewaidy and Alyousef (2018) found insignificant effects.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations